2014
DOI: 10.1002/ejic.201402152
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Urchin‐Like FeF2 Nanoarchitectures and Their Conversion into Three‐Dimensional Urchin‐Like Mesoporous α‐Fe2O3 Nanoarchitectures for Methane Activation

Abstract: Novel urchin‐like FeF2 nanoarchitectures have been fabricated by an unconventional nonhomogeneous ionic liquid/diphenyl ether solvothermal method. Subsequent solid‐state thermal annealing was utilized to convert the FeF2 nanoarchitectures into 3D urchin‐like mesoporous α‐Fe2O3 nanoarchitectures. The reaction system and temperature played important roles in the morphology of FeF2 and the growth of the 3D urchin‐like α‐Fe2O3. A study of methane activation over the 3D urchin‐like mesoporous α‐Fe2O3 nanoarchitectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…However, its reactivity improves when coupled with oxides such as Al 2 O 3 . , The redox process of Fe 2 O 3 /Al 2 O 3 proceeds at a high rate from Fe 2 O 3 to Fe 3 O 4 due to the mechanism of Avrami Erofe’ev phase change. Recent studies have shown that nanostructured hematite α-Fe 2 O 3 exhibits high catalytic activity toward CH 4 activation and conversion into CO 2 (at 230 °C) due to increased surface area and high oxygen vacancy density of the mesoporous structures …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its reactivity improves when coupled with oxides such as Al 2 O 3 . , The redox process of Fe 2 O 3 /Al 2 O 3 proceeds at a high rate from Fe 2 O 3 to Fe 3 O 4 due to the mechanism of Avrami Erofe’ev phase change. Recent studies have shown that nanostructured hematite α-Fe 2 O 3 exhibits high catalytic activity toward CH 4 activation and conversion into CO 2 (at 230 °C) due to increased surface area and high oxygen vacancy density of the mesoporous structures …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that nanostructured hematite α-Fe 2 O 3 exhibits high catalytic activity toward CH 4 activation and conversion into CO 2 (at 230 °C) due to increased surface area and high oxygen vacancy density of the mesoporous structures. 18 Jin et al studied CH 4 oxidation pathways on O 3 −Fe−Fe iron oxide termination in an oxygen-rich environment. The study was based on periodic density functional theory (DFT) calculations 19 in which O 2 competes with the iron oxide to react with CH 4 , and the atmospheric O 2 can quickly recover the surface oxygen of iron oxide.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years,w eh ave explored the activation of the CÀHb onds in methanea nd find that the CÀHb onds of methane can be activated and converted to CÀOb onds over the urchin-like a-Fe 2 O 3 at 230 8C, which is al ower temperature than achievedo ver common a-Fe 2 O 3 as the catalyst. [20] In the current investigation,a na stonishing phenomenon was observedi nw hich the CÀHb onds in methanec an be activated over mesoporous a-Fe 2 O 3 at 140 8C, which is very rare in heterogeneous catalysis.B ased on the results of the comprehensive comparison study on mesoporous a-Fe 2 O 3 and other a-Fe 2 O 3 nanomaterials with different morphology,itwas concluded that the surfaces tructures of the hole wall in the mesoporous a-Fe 2 O 3 playeda ni mportant role in the activation of the CÀHb onds in methane. This discovery mayp rovideanew way of thinking about designing and preparing highlyeffective heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 61%
“…During the past few years, we have explored the activation of the C−H bonds in methane and find that the C−H bonds of methane can be activated and converted to C−O bonds over the urchin‐like α‐Fe 2 O 3 at 230 °C, which is a lower temperature than achieved over common α‐Fe 2 O 3 as the catalyst . In the current investigation, an astonishing phenomenon was observed in which the C−H bonds in methane can be activated over mesoporous α‐Fe 2 O 3 at 140 °C, which is very rare in heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 61%
“…They found that CH 4 was converted into products containing C–O bonds (CO 2 ) at 230°C, which is 190°C lower than over bulk α-Fe 2 O 3 . As for the reason, with the measurement and comparison of adsorbed oxygen on the two material, they inferred that the urchin-like α-Fe 2 O 3 nanoarchitectures have a higher density of surface oxygen vacancies than bulk α-Fe 2 O 3 , which can accelerate the dissociation of oxygen molecules at the surface and increase the mobility of lattice oxygen ( Dong et al, 2014 ). It should be noted that this structure does not exhibit good CH 4 conversion at high temperatures (700°C, conversion = 16%).…”
Section: Transition Metal Oxides For Catalytic Ch 4 ...mentioning
confidence: 99%